Research in consumer behavior. Vol. 10 - Belk, Russell W. (Emerald, 2006)
Volume 10 of "Research in Consumer Behavior" presents a wide range of cutting edge consumer behavior research using both quantitative and qualitative research methods. The topics addressed include self-gifts, souvenirs, grocery coupon proneness, socialization, acculturation, tattooing, possession attachment, consumer decision making, information acquisition, and meaning making through consumption. As this rich set of topics suggests, this is a volume that will interest academics, practitioners, and students of consumer behavior. The book is international in scope and uses a qualitative and quantitative approach to consumer behavior research.
Keywords: Business & Economics -- Management.; Social Science -- General.; Society & social sciences.; Consumer behavior.; elektronické knihy; electronic books